2005
DOI: 10.1016/j.jacc.2005.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Inappropriate Peripheral Vascular Responses in Hypertrophic Cardiomyopathy

Abstract: Paradoxical vasodilatation during LBNP occurs in 40% of patients with ABPR during exercise and is reversed by propranolol, clonidine, and paroxetine. Paroxetine also improved SBP response to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…Beta-blockers could influence heart rate and blood pressure during exercise, and plasma levels of BNP [22][23][24]. However study findings were similar before and after statistical adjustment for betablocker treatment, and when patients taking beta-blockers were excluded from the analysis.…”
Section: Study Limitationsmentioning
confidence: 75%
“…Beta-blockers could influence heart rate and blood pressure during exercise, and plasma levels of BNP [22][23][24]. However study findings were similar before and after statistical adjustment for betablocker treatment, and when patients taking beta-blockers were excluded from the analysis.…”
Section: Study Limitationsmentioning
confidence: 75%
“…excessive fall in peripheral/systemic vascular resistance) 19 . It has also been suggested that lower exercise capacity and ABPR in HC may be related to diastolic dysfunction 20 and a blunted augmentation of stroke volume during exercise 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The recent demonstration of recurrent abrupt spontaneous episodes of hypotension during daily activities associated with a fall in systemic vascular resistance suggests that abnormal vascular control mechanisms may also explain some episodes of non-exercise-related syncope. 11 Data on tilt testing in patients with hypertrophic cardiomyopathy and syncope are relatively scant. In 1 small study, head-up tilt at 60°for 45 minutes resulted in a fall in mean arterial pressure and reflex hypotension in 82% of syncopal patients compared with 26% of nonsyncopal patients and 22% of control subjects.…”
Section: Causes Of Syncope In Hypertrophic Cardiomyopathymentioning
confidence: 99%